Enhancing Consumer Trust and Purchase Decisions Through Online Reviews and Hedonic Factors: A Study of Coffee Shops in Jakarta (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to determine how online reviews and hedonic factors influence trust and purchase decisions. The population of this research comprises consumers from 10 retail coffee shop brands located in Jakarta, with a sample size of 208 people. The sampling technique used is snowball sampling. The data analysis method combines quantitative and descriptive approaches. Quantitative data analysis employs the Structural Equation Model (SEM) with the help of LISREL software. The results show that online reviews, hedonic factors, and trust have a direct impact on purchase decisions. Additionally, trust can serve as a mediating variable between online reviews and hedonic factors in relation to purchase decisions. This study provides valuable insights for coffee shop business practitioners in managing online reviews, creating enjoyable experiences, and designing more effective marketing strategies to enhance consumer trust and influence purchase decisions.